Measurement of Body Image Satisfaction Using Computer Manipulation of a Digital Image. - Sands, Rob; Maschette, Wayne; Armatas, Christine (Journal of Psychology, 2004)
The authors investigated a method for assessing body image satisfaction based on computer manipulation of a digitized image of self using a sample of 56 female students aged 17 to 22 years. The total percentage change when re-sizing the actual image to the ideal by the computer adjustment method was significantly correlated with the figural/silhouette discrepancy method. Both of these measures were correlated significantly with body part satisfaction and body mass index but not with social physique anxiety. Although for this sample the 2 methods yielded similar results, the computer adjustment method addresses several limitations of the figural/silhouette method, such as scale coarseness and the accuracy of proportional change between figural/silhouettes. Furthermore, by using the individual's actual image, potential confounds associated with stylized figure drawings that are typically based on Caucasian physical features are removed. Finally, this method also takes into account the importance of various body parts for determining body image satisfaction. Reprinted by permission of the publisher.